When finance captures labor's capital: Dominant personal pensions, resurgent occupational provision in Central and Eastern Europe - Naczyk, M (Wiley, 2018)
While in Western Europe occupational plans dominate private pension provision, coverage of such plans is marginal in Central and Eastern Europe (CEE). Previous literature has shown the World Bank’s instrumental role in persuading CEE countries to divert part of their social security contributions towards mandatory personal pensions. The dominance of the Bank’s model of pension privatization from the mid-1990s largely explains the marginalization of occupational plans. However, as this model has been challenged since the late 2000s, occupational pensions have re-appeared on the agenda. To shed light on the changing politics of occupational pensions, this paper focuses on the role of organized interests – namely employers’ associations, trade unions and financial groups – that are key players in Western Europe, but whose role has been understudied in CEE. The paper follows these actors’ activities in the last three decades of pension politics in Poland, i.e. one of the few CEE countries to have promoted occupational provision. It shows that, although organized interests had limited policy expertise and mainly mobilized social consent for – or opposition to – reform in the early phases of post-communist pension reform, the growing organizational resources of business groups – in contrast with unions – make them increasingly influential actors in reshaping the contours of CEE private pension provision.